The effect of northeast monsoon on the physical chemical parameters and dfe(iii) ions at Pulau Redang, Terengganu - Mohamed @ Mohd Ramli, Khairul Nizam; Amiruddin, Abd Muhaimin; Ramjam, Nur Jannati (UMT Press, 2024)
The physical-chemical parameters and dissolved Fe(III) ion distribution (dFe(III)) were determined throughout the water column at Pulau Redang, Terengganu. This study was carried out during March 2019 and October 2019 to evaluate the possible effect of northeast monsoon (NEM) on the pH, salinity, dissolved oxygen, turbidity, conductivity, and dFe(III) ion concentration. The determination of dFe(III) ion was obtained by using the optimised adsorptive-cathodic stripping voltammetry (AdCSV) method. The results show a change in physical and chemical conditions between March 2019 and October 2019 is due to the seasonal northeast monsoon phenomenon. However, there was no significant difference (p>0.05) between the concentration of dFe(III) ions in March 2019 and October 2019. This indicated that this seasonal NEM does change the physical chemical condition of the water column and does not affect the Fe(III) ion distribution in our study area.